Transfer of CVD-grown graphene for room temperature gas sensors. (13th September 2017) - Rigoni, F; Maiti, R; Baratto, C; Donarelli, M; MacLeod, J; Gupta, B; Lyu, M; Ponzoni, A; Sberveglieri, G; Motta, N; Faglia, G
Abstract: An easy transfer procedure to obtain graphene-based gas sensing devices operating at room temperature (RT) is presented. Starting from chemical vapor deposition-grown graphene on copper foil, we obtained single layer graphene which could be transferred onto arbitrary substrates. In particular, we placed single layer graphene on top of a SiO2 /Si substrate with pre-patterned Pt electrodes to realize a chemiresistor gas sensor able to operate at RT. The responses to ammonia (10, 20, 30 ppm) and nitrogen dioxide (1, 2, 3 ppm) are shown at different values of relative humidity, in dark and under 254 nm UV light. In order to check the sensor selectivity, gas response has also been tested towards hydrogen, ethanol, acetone and carbon oxide. Finally, a model based on linear dispersion relation characteristic of graphene, which take into account humidity and UV light effects, has been proposed.